MAGNETIC PHASE TRANSITIONS IN TRANSITIONAL METAL OXIDES STUDIED WITH PERTURBED ANGULAR CORRELATIONS - BARTOS, A.; WIARDA, D.; INGLOT, Z.; LIEB, K. P.; UHRMACHER, M.; WENZEL, T. (International journal of modern physics. B, Condensed matter physics, statistical physics, applied physics, 1993)
The Perturbed Angular Correlation (PAC) method with radioactive tracer nuclei is well-suited to study the critical behaviour of magnetic hyperfine fields. Here we present the results of PAC measurements with 111Cd probes, concerning the antiferromagnetic phase transitions in CuO, Co3O4 and MnO. The measured Larmor frequencies were fitted with a Curie-Weiss type temperature dependence ωL(T)/ωL(0) = (1-T/TN)β. In CuO the PAC probe is subject to a high electric field gradient (efg) with the coupling constant νQ = 434(2) MHz and the asymmetry parameter η = 0.42(1). Therefore, combined electric/magnetic hyperfine interaction is observed below TN. Similar to neutron diffraction experiments, a second magnetic transition was observed at T1 = 213 K. The analysis of the PAC data gave TN = 224(2) K and β = 0.33(1) for T1 ≤ T ≤ TN. In the spinel Co3O3, the measured critical parameters for 111Cd at cation sites with tetrahedral oxygen coordination are TN = 39(1) K and β = 0.34(2). This site has a nearly cubic oxygen coordination and therefore a vanishing efg. In Mn1−xO (defective NaCl structure, x ≤ 0.15), the critical parameters were found to sensitively depend on the annealing conditions. They will be discussed in comparison with those in Fe1−xO.